The Role of Riddle Games in EFL Classrooms - Aliyeva Navruza Habibullayevna; Otaxonova Nurjahon Ilhomjon Qizi (Researchparks Publishing, 2022)
This article is devoted to the role of riddles in teaching English. The article provides several benefits of riddles for use in English lessons. Using this interactive method in English classes makes learning process more useful and interesting. The aim of usage of riddles is to develop students ‘speaking skills, vocabulary as well as their critical thinking and working as a team.